Från ordlista till ordbok. Utvecklingen av den finsk-svenska ordboken från 1600-talet till idag - Romppanen, Birgitta (LexicoNordica, 2000)
The first dictionary containing Finnish as a target language appeared in 1637. It was a general language glossary, of which the source language was Latin. The interest was now focused on the Finnish language, owing to its status of source language in Juslenius’s Finskt Orda-Boks Försök/Suomalaisen Sana-Lugun Coetus that was published in 1745. This made the bi- and multilingual dictionaries become descriptive reading comprehension dictionaries of Finnish. With this, the codification of Finnish began, a process, however, that was not carried out until the period 1951–61, during which the monolingual prescriptive dictionary Nykysuomen sanakirja was published. A big step in the change from a Finnish reading comprehension dictionary into a reading comprehension dictionary for Finnish combined with a production dictionary for Swedish was taken in 1908 through Knut Cannelin’s. Finskt-svenskt lexikon/ Suomalais-ruotsalainen sanakirja. The electronic dictionary that now, in the beginning of the 21st century, is in a phase of strong progress implies a new structural development for the monolingual and bilingual Finnish dictionaries.